2016
DOI: 10.1021/acs.energyfuels.6b03257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supercritical Carbon Dioxide Treatment Time, Pressure, and Temperature on Shale Water Wettability

Abstract: Supercritical carbon dioxide (SC-CO 2 ) fluid can dissolve surface matter on shale and, thus, change the surface properties of shale. To study the influence of SC-CO 2 on the water wettability of shale, shale samples collected from the Longmaxi formation in Sichuan Basin were treated with SC-CO 2 at various time intervals, pressures, and temperatures. The results show that, after SC-CO 2 treatment, the ratio of C and Si in the shale increased, while the ratio of O, Ca, Mg, and H decreased. Water was released f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 39 publications
1
51
0
Order By: Relevance
“…10 Due to the characteristics of supercritical carbon dioxide (Sc-CO 2 ), including its low viscosity, high diffusion capacity near gas and high density near liquid, it has unique advantages for the shale gas extraction. 11 Additionally, much research has shown that preferential adsorption of carbon dioxide over methane, which indicates the feasibility of CO 2 sequestration with enhanced gas recovery (CS-EGR) in shale reservoirs. 12,13 Although the CS-EGR technique in shale has not yet been widely commercialized, extensive investigations have been carried out in this eld.…”
Section: Introductionmentioning
confidence: 99%
“…10 Due to the characteristics of supercritical carbon dioxide (Sc-CO 2 ), including its low viscosity, high diffusion capacity near gas and high density near liquid, it has unique advantages for the shale gas extraction. 11 Additionally, much research has shown that preferential adsorption of carbon dioxide over methane, which indicates the feasibility of CO 2 sequestration with enhanced gas recovery (CS-EGR) in shale reservoirs. 12,13 Although the CS-EGR technique in shale has not yet been widely commercialized, extensive investigations have been carried out in this eld.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, enormous work was directed towards understanding the fundamentals of the CO 2 -shale interaction at reservoir conditions for better CCS applications [42][43][44][45][46][47][48][49][50][51][52], by evaluating the impact of CO 2 injection on shales. Earlier in 2008, Busch et al [53] found that the rock properties of Muderong shale in Australia were affected by the dissolution behavior of SCCO 2 .…”
Section: Ccs In Shalesmentioning
confidence: 99%
“…Hence, it is necessary to address the complex nature of shales' wettability and analyze the factors involved, i.e., pressure, temperature, pH, mineral composition and TOC [85]. Several studies were conducted to evaluate the wetting behavior of different types of shales at the presence of different fluids, by using different methods and techniques, such as equilibrium contact angle (sessile drop) [44,[86][87][88][89][90], NMR [91], spontaneous imbibition [92][93][94][95][96], and liquid-liquid extraction [87].…”
Section: Surface Wettabilitymentioning
confidence: 99%
“…This is because temperature influences the supercritical fluid density. Under the same pressure, the density of ScCO 2 decreases as temperature increases, and the solubility of ScCO 2 decreases [50,51].…”
Section: Ir Indexmentioning
confidence: 99%